Omnichannel Marketing Model Applied at the Shopping Centers in Medellín City - Rodríguez Salazar, María Isabel (Mercados y Negocios, 2022)
The main objective of this research is to form an omnichannel marketing model applied at the shopping centers in Medellín city. For this, a qualitative methodology was applied. Two (2) focus groups with shopping center customers, two (2) in-depth interviews with experts in Omnichannel, Sandiego Shopping Center case study, and a theoretical review were carried out to obtain the fundamental components of the omnichannel marketing model applied to this category. The model is proposed in a circular structure, made up of orbits that revolve around the Omni-client. The model is made up of the consumer’s journey, from 5A; the levels of transparency, coherence, and fluidity based on: (+) Greater consistency = (+) Greater loyalty; and the levels of online and offline interaction, which are transversal in the entire proposal of the model.